COLLECTION OF MATERIAL DNA SAMPLES FROM BIRDS IN THE GUNUNG HALIMUN NATIONAL PARK (GHNP) FOR ESTABLISHING OF DNA BANK - Sulandari, Sri; Astuti, Dwi; Kundarmasno, Agus; Marakarmah, Alwin; Wijamukti, Satrio (Research Center for Biology-Indonesian Institute of Sciences, 2001)
This study was conducted to collect material DNA samples from birds in the Gunung Halimun National Park (GHNP) for establishing of DNA bank.Ciptarasa, Geger Hanjuang and Cikaniki village areas were chosen as sites for sample collections in the GHNP.In order to take the sample from birds, transect lines were established at each site where series of mist nets were operated.The captured birds, both live- and died-birds, were identified. For the living birds, blood and/or shed feathers were taken from the bird prior to releasing.In case of died birds, tissue and liver were collected. The collected samples were transported to genetic laboratory at Zoological Division,Researh Center for Biology (RCB)-LIPI (The Indonesian Institute of Science) and kept in 4Â°C. In this collection, a total of 411 collected samples were obtained, coming from 25 families and 79 species.The 19-endemic birds were found in GHNP.